ANALISIS PENGARUH KUALITAS WEBSITE TERHADAP KEPUASAN MAHASISWA STIE PERBANAS SURABAYA MENGGUNAKAN METODE WEBQUAL - adrianto, shandi prima yudha; Sulistiowati, Sulistiowati; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
School of Economics PERBANAS Surabaya (STIE PERBANAS) is an Educational Institution in the field of Business and Banking. To support its development, use of information technology such as the Website is needed aimed at information and communication media. However, there are websites that haven’t be able to improve the ranking based on the number of visitors. Based on data from a website that presents the rank of the number of visitors, until the month of November 2015 global ranking of the website to be at 640 097 in the rankings while Indonesia is at 16,082. This study was to look into the matter by analyzing the relationship between the quality of the website and user satisfaction (students). From questionnaires conducted obtained a sample of 75 respondents. Data from the questionnaire testing the variables with the validity and reliability. The next test and test data normality assumption as a condition for the implementation of the next step, regression linear analysis. Based the test results it was concluded that the variable quality of use is not positive and significant impact. While the information of quality and the quality of the interaction of positive and significant impact on user satisfaction (students).